Bilateral Sequential Cochlear Implantation in Patients With Enlarged Vestibular Aqueduct (EVA) Syndrome. Issue 2 (February 2016) - Manzoor, Nauman F.; Wick, Cameron C.; Wahba, Marian; Gupta, Amit; Piper, Robin; Murray, Gail S.; Otteson, Todd; Megerian, Cliff A.; Semaan, Maroun T.
Abstract : Objectives: To analyze audiometric outcomes after bilateral cochlear implantation in patients with isolated enlarged vestibular aqueduct (EVA) syndrome and associated incomplete partition (IP) malformations. Secondary objective was to analyze rate of cerebrospinal fluid (CSF) gusher in patients with IP-EVA spectrum deformities and compare this with the existing literature. Study Design: Retrospective chart review. Methods: Thirty-two patients with EVA syndrome who received unilateral or bilateral cochlear implants between June 1999 and January 2014 were identified in the University Hospitals Case Medical Center cochlear implant database. Isolated EVA (IEVA) and Incomplete Partition Type II (IP-II) malformations were identified by reviewing high-resolution computed tomography (HRCT) imaging. Demographic information, age at implantation, surgical details, postimplantation audiometric data including speech reception thresholds (SRT), word, and sentence scores were reviewed and analyzed. Intra- and postoperative complications were analyzed as well and compared with the literature. Results: Seventeen patients (32 implanted ears) had pediatric cochlear implantation for EVA-associated hearing loss. Data from 16 controls (32 implanted ears) were used to compare audiometric and speech outcomes of EVA cohort. Mean age at implantation was 6.8 years for EVA cohort and 6.0 years for controls. There was no statistically significant difference in long-term postoperative SRT, monaurally aided word scores, and binaurally tested word scores between pediatric EVA group and controls. The EVA patients had a long-term mean sentence score of 85.92%. A subset of EVA patients implanted at mean age of 3.18 years (n = 15 ears) had similar audiometric outcomes to another control group with Connexin 26 mutations (n = 20 ears) implanted at a similar age. Further subset analysis revealed no significant differences in age at implantation, SRT, and word scores in patients with IEVA and IP-II malformation. There was no significant association between size of vestibular aqueduct and age at implantation. There was no CSF gusher or other intra- or postoperative complications reported in our series. Conclusion: Bilateral sequential cochlear implantation can be performed safely in patients with EVA. Audiometric outcomes are excellent and comparable to pediatric cochlear implant patients with no malformations. CSF gusher rates can be minimized by trans-round window approach. Further long-term studies are needed to identify differences within IP-EVA spectrum deformities, audiometric outcomes, and proportions of EVA patients who will need cochlear implantation for hearing rehabilitation.